Tripartite chimeric pseudogene from the genome of rice blast fungus Magnaporthe grisea suggests double template jumps during long interspersed nuclear element (LINE) reverse transcription - Gogvadze, Elena (BioMed Central, 2007)
BACKGROUND: A systematic survey of loci carrying retrotransposons in the genome of the rice blast fungus Magnaporthe grisea allowed the identification of novel non-canonical retropseudogenes. These elements are chimeric retrogenes composed of DNA copies from different cellular transcripts directly fused to each other. Their components are copies of a non protein-coding highly expressed RNA of unknown function termed WEIRD and of two fungal retrotransposons: MGL and Mg-SINE. Many of these chimeras are transcribed in various M. grisea tissues and during plant infection. Chimeric retroelements with a similar structure were recently found in three mammalian genomes. All these chimeras are likely formed by RNA template switches during the reverse transcription of diverse LINE elements. RESULTS: We have shown that in M. grisea template switching occurs at specific sites within the initial template RNA which contains a characteristic consensus sequence. We also provide evidence that both single and double template switches may occur during LINE retrotransposition, resulting in the fusion of three different transcript copies. In addition to the 33 bipartite elements, one tripartite chimera corresponding to the fusion of three retrotranscripts (WEIRD, Mg-SINE, MGL-LINE) was identified in the M. grisea genome. Unlike the previously reported two human tripartite elements, this fungal retroelement is flanked by identical 14 bp-long direct repeats. The presence of these short terminal direct repeats demonstrates that the LINE enzymatic machinery was involved in the formation of this chimera and its integration in the M. grisea genome. CONCLUSION: A survey of mammalian genomic databases also revealed two novel tripartite chimeric retroelements, suggesting that double template switches occur during reverse transcription of LINE retrotransposons in different eukaryotic organisms.